Presencia y origen de rocas sedimentarias en el basamento ofiolítico de Costa Rica - Jürgen Gursky, Hans (2011)
Different types of sedimentary rocks intercalated between basalts of the Nicoya Ophiolite Complex (Jurassic to Lower Tertiary, Costa Rica and western Panama) were studied using sedimentologic, petrographic, X-ray diffractonal, chemical, and fields methods. They occur as regionally extended sequences up to tens of meters thick, thin lenses, inter and intrapillow sediment, xenoliths, intrusive jasper bodies, tectonic blocks, and volcaniclastic material. Radiolarite sequences containing in places sedimentary manganese nodules, were formed below the CCD in the eastern equatorial Pacif Ocean under 02 -rich, deep-sea conditions with little detrial input and very low-energy currents. Lenses of fine-grained tuffite and detrius-rich chert were deposited in local ponds. Dikes of non-bedded jasper with colloidal structures may represent hydrothermal mineralizations or thermally mobilized radiolarite material. Lenses of pelagic foraminiferal limestone are present close to the top of the Nicoya Complex and were deposited below the CLy. Volcaniclastic breccias and sandstones represent locally-derived debris from basalt flows and fault scarps.The change from siliceous, Jurassic to middle Cretaceous, to calcareous, upper Cretaceous, sedimentation relfects the late Mesozoic world-wide lowering of the CCD and varitions in regional igneous and platetectonic morphology. The date make a contribution to the reconstrution of the  geodynamic evolution of the Nicoya Complex.